MODERN APPROACHES TO DIAGNOSIS AND TREATMENT OF URETHRAL STRICTURES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Urethral stricture remains one of the most clinically challenging conditions in reconstructive urology, demanding precise diagnostic evaluation and individualized treatment selection. This article reviews contemporary diagnostic modalities and surgical techniques - including drug-coated balloon dilation, buccal mucosal graft urethroplasty, and endoscopic urethrotomy - with emphasis on comparative outcome data and evidence-based treatment algorithms from current international guidelines.